Insulin Treatment Perception and Factors affecting the Acceptance in Type 2 Diabetes Mellitus Patients attending a Specialist Clinic in Ilorin, Nigeria - Agede, Olalekan A.; Olarinoye, John Kola; Ogunmodede, James Ayodele; Sanni, Nasiru; Bojuwoye, Matthew Olumuyiwa; Opeyemi, Christopher Muyiwa; Ologe, Mary Olufunmilayo; Oyedepo, Dapo S (Journal of Tropical Pharmacy and Chemistry, 2024)
Type 2 Diabetes Mellitus (T2DM) is a significant global health challenge, with increasing prevalence and diverse management approaches. Insulin therapy, a cornerstone in the management of advanced T2DM, is often met with reluctance and negative perceptions. A better understanding of the multifaceted factors influencing insulin acceptance is crucial for tailored interventions. This study explored the perception regarding insulin treatment using the validated Insulin Treatment Appraisal Scale (ITAS). This study aimed to explore socio-demographic and clinical factors influencing insulin therapy perception and acceptance among T2DM patients in Ilorin, Nigeria. It was a cross-sectional study among T2DM patients. Data on socio-demographic characteristics, diabetes related features and ITAS were collected and analyzed. Statistical methods, including t-tests and chi square were employed to assess the impact of various variables on insulin treatment perception. There was a statistically significant difference (p=0.029) between the age of insulin naïve and experienced patients. Some insulin-experienced patients had positive perceptions of insulin, like their belief in insulin’s health benefits (p = 0.001) and ability to control blood glucose (p = 0.048). Insulin-naive individuals exhibited more negative attitudes toward insulin, emphasizing the need for targeted interventions and patients’ health education. This study provides valuable insights into the intricate interplay of socio-demographic characteristics, diabetes related features, and individual perceptions influencing insulin therapy acceptance among participants with T2DM. The findings underscore the importance of personalized interventions to address negative perceptions, ultimately enhancing diabetes management and treatment outcome.